2015
DOI: 10.1007/s10646-015-1472-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and vertical distribution of bacterial community in the northern South China Sea

Abstract: Microbial communities are highly diverse in coastal oceans and response rapidly with changing environments. Learning about this will help us understand the ecology of microbial populations in marine ecosystems. This study aimed to assess the spatial and vertical distributions of the bacterial community in the northern South China Sea. Multi-dimensional scaling analyses revealed structural differences of the bacterial community among sampling sites and vertical depth. Result also indicated that bacterial commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…The stacked bar graph of the microbial community in this study displayed the dominant species in the grouper rearing seawater: Bacteroidetes, Proteobacteria, Cyanobacteria, Actinobacteria, and Firmicutes. This result is in accordance with other studies indicating that these bacterial phyla occupy the dominant ecological niches within seawater ecosystems (Sun et al, 2015;Zhang et al, 2021). This study showed significant differences in the phyla Planctomycetes and Fusobacteria.…”
Section: Discussionsupporting
confidence: 93%
“…The stacked bar graph of the microbial community in this study displayed the dominant species in the grouper rearing seawater: Bacteroidetes, Proteobacteria, Cyanobacteria, Actinobacteria, and Firmicutes. This result is in accordance with other studies indicating that these bacterial phyla occupy the dominant ecological niches within seawater ecosystems (Sun et al, 2015;Zhang et al, 2021). This study showed significant differences in the phyla Planctomycetes and Fusobacteria.…”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, cyanobacteria taxa have often been observed in the Pearl River Estuary (Sun et al 2011(Sun et al , 2012(Sun et al , 2015 and these studies have indicated that cyanobacteria are the dominant group in this estuarine sediment. However, no studies on the ecological distribution of cyanobacteria in the Pearl River Estuary sediment have been reported.…”
Section: Introductionmentioning
confidence: 79%
“…The physicochemical factors play an important role in shaping the structure of marine microbial communities and cause variations at spatial scales (Wang et al, 2019). Recent studies have also shown that variations in the community composition of marine bacteria as well as patterns of worldwide bacterial (16S) diversity and community structure are strongly correlated with temperature and DO (Sun et al, 2015; James et al, 2022).…”
Section: Discussionmentioning
confidence: 99%